2013
DOI: 10.3390/bs3010099
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of Abnormal Behavior in Adult Ex-laboratory Chimpanzees (Pan troglodytes) Following Re-socialization

Abstract: Adverse rearing conditions are considered a major factor in the development of abnormal behavior. We investigated the overall levels, the prevalence and the diversity of abnormal behavior of 18 adult former laboratory chimpanzees, who spent about 20 years single caged, over a two-year period following re-socialization. According to the onset of deprivation, the individuals were classified as early deprived (EDs, mean: 1.2 years) or late deprived (LDs, mean: 3.6 years). The results are based on 187.5 hours of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…In other words, the chimpanzees rated higher on Anxiety were those who had been victims of the bushmeat trade plus being a pet or tourist attraction, with the longest isolation during infancy and juvenility and a high humanization degree. These findings are consistent with the previous literature relating to early life stress where the adversities experienced at a young age were related to aspects like maternal separation (Botero et al, 2013;Reimers et al, 2007;Latham & Mason, 2008), deprivation degree (Reimers et al, 2007;Kalcher-Sommersguter et al, 2013) or human exposure (Freeman & Ross, 2014), among others. These are all important antecedents that can affect personality outcomes, especially for anxiety or similar personality aspects related to stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, the chimpanzees rated higher on Anxiety were those who had been victims of the bushmeat trade plus being a pet or tourist attraction, with the longest isolation during infancy and juvenility and a high humanization degree. These findings are consistent with the previous literature relating to early life stress where the adversities experienced at a young age were related to aspects like maternal separation (Botero et al, 2013;Reimers et al, 2007;Latham & Mason, 2008), deprivation degree (Reimers et al, 2007;Kalcher-Sommersguter et al, 2013) or human exposure (Freeman & Ross, 2014), among others. These are all important antecedents that can affect personality outcomes, especially for anxiety or similar personality aspects related to stress.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, due to the genetic, biological, and psychological proximity, nonhuman primates have been preferred as a comparative animal model to understand what triggers early life stress products in humans (Gilmer & McKinney, ; Nelson & Winslow, ). Decades of studies revealed that early impoverished, neglected, and abused primates show long‐term effects on cortical organization (Bogart, Bennett, Schapiro, Reamer, & Hopkins, ), cognitive deficits (Davenport, Rogers, & Rumbaugh, ), greater expression of abnormal and stereotyped behaviors (Birkett & Newton‐Fisher, ; Kalcher‐Sommersguter, Franz‐Schaider, Preuschoft, & Crailsheim, ; Latham & Mason, ), less social and sexual behaviors (Freeman & Ross, ; Kalcher‐Sommersguter et al, ; Llorente, Riba, Ballesta, Feliu, & Rostán, ), attachment disorders (van Ijzendoorn, Bard, Bakermans‐Kranenburg, & Ivan, ), anxiety (Botero, Macdonald, & Miller, ), increased inactivity (Llorente et al, ), neophobia (Ueno & Matsuzawa, ), and higher stress sensitivity (Reimers, Schwarzenberger, & Preuschoft, ), than mother‐reared and normal developed chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings regarding change of behaviors and welfare over time reflect those chimpanzees taken from their mothers and housed alone throughout their lives can recover if introduced into a social group in late adulthood (Kalcher-Sommersguter et al 2013;Reimers et al 2007). Other studies conducted at African sanctuaries with management strategies that allow deprived infant chimpanzees to express speciestypical behaviors and improve their cognitive skills also found low rates of aberrant behaviors (Ongman et al 2013;Wobber and Hare, 2011).…”
Section: Influences On Recoverymentioning
confidence: 58%
“…The goal is to promote the development of species-typical behaviors, by enhancing their welfare and social skills. Several studies have determined that chimpanzees with a previous history of maltreatment or unfavorable rearing conditions can be rehabilitated and resocialized over time (Kalcher-Sommersguter et al 2013;Kalcher et al 2008). However, most of this evidence comes from former laboratory chimpanzees (Reimers et al 2007), where chimpanzees that were caged singly at an early age (mean 1.2 yr) present higher levels of social competence than those caged singly at a later age (mean 3.6 yr) (Kalcher-Sommersguter et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One challenging aspect of the choice concept is striking a balance between what is best for the animal, for example, tending to the animals' need for physical exercise and to benefit from being outdoors in nice weather (e.g., vitamin D from the sun) with their need to “feel safe” indoors in smaller areas. Although data measuring the impact of different life histories in relation to choice are lacking, there has been a recent focus on the long‐term outcomes for chimpanzees with atypical life histories (e.g., former entertainment or pet chimpanzees [Ross and Vreeman, ]; former biomedical laboratory chimpanzees [Kalcher‐Sommersguter et al, ]). The question of providing optimal levels of choice without compromising welfare is likely to be an on‐going discussion and challenge for zoos and sanctuaries, particularly in relation to animals with atypical life histories.…”
Section: Discussionmentioning
confidence: 99%